STRATEGY TO ATTRACT NEW CUSTOMERS: A CASE OF PROFESSIONAL PRODUCT HOMEMADE - Andrea Desmita Liusvia; Mahfudz Mahfudz; Afina Hasya (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT The present study endeavors to ascertain the branding strategies of Homemade, a fledgling enterprise that were established in the year 2021, in the wake of the COVID-19 pandemicinduced isolation. With the closure of several socializing avenues, people have been grappling with feelings of seclusion and detachment. Homemade, with its focus on food, aims to bridge this gap and foster a sense of community among people. As a nascent startup, Homemade is confronted with several challenges, including a lack of brand recognition and the identification of an optimal marketing plan. These issues are compounded by the company's limited workforce and a dearth of online and offline marketing initiatives. Therefore, this research project is designed to furnish Homemade with recommendations to surmount these challenges and identify the root cause of the problem. One of the proposed marketing strategies for Homemade is to leverage the influence of local social media personalities to promote its culinary offerings. This can be achieved through a collaborative effort whereby Homemade sends free food samples to influencers for review and promotion. Such an approach can potentially enhance the company's visibility and augment its customer base